2007
DOI: 10.1093/aob/mcl226
|View full text |Cite
|
Sign up to set email alerts
|

Solar Ultraviolet-B Radiation and Insect Herbivory Trigger Partially Overlapping Phenolic Responses in Nicotiana attenuata and Nicotiana longiflora

Abstract: The results suggest that the anti-herbivory effect induced by UV-B may be mediated at least in part by the accumulation of phenylpropanoid derivatives that are similar to those induced by the plant in response to insect herbivory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
139
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 59 publications
(75 reference statements)
7
139
0
3
Order By: Relevance
“…Tais substâncias são frequentes em xerófitas e provavelmente reduzem a passagem de luz através das células epidérmicas, protegendo contra o excesso de radiação solar (IZAGUIRRE et al, 2007) que pode ter efeitos deletérios sobre as plantas como danos por radiação ultravioleta, estresse induzido por aquecimento das folhas e fotoinibição resultante da exposição a níveis altos de luz que danificam o sistema fotossintético (JORDAN; DILLON;WESTON., 2005). A falta de água causa perda de turgor nas células-guarda, o fechamento dos estômatos e, por sua vez, diminui o dióxido de carbono disponível limitando a fotossíntese; isto aumenta o estresse oxidativo e pode induzir o acúmulo de compostos fenólicos (CLOSE;MCARTUR, 2002).…”
Section: Resultsunclassified
“…Tais substâncias são frequentes em xerófitas e provavelmente reduzem a passagem de luz através das células epidérmicas, protegendo contra o excesso de radiação solar (IZAGUIRRE et al, 2007) que pode ter efeitos deletérios sobre as plantas como danos por radiação ultravioleta, estresse induzido por aquecimento das folhas e fotoinibição resultante da exposição a níveis altos de luz que danificam o sistema fotossintético (JORDAN; DILLON;WESTON., 2005). A falta de água causa perda de turgor nas células-guarda, o fechamento dos estômatos e, por sua vez, diminui o dióxido de carbono disponível limitando a fotossíntese; isto aumenta o estresse oxidativo e pode induzir o acúmulo de compostos fenólicos (CLOSE;MCARTUR, 2002).…”
Section: Resultsunclassified
“…The involvement in the stress response of chlorogenic acid has been reported, with its concentration increasing in lettuce upon wounding, and in tobacco upon both UV-B irradiation and insect feeding (Cantos et al 2001;Izaguirre et al 2007). In globe artichoke, we have recently shown that exposure to UV-C consistently increases the level of the major dicaffeoylquinic acid isomer, while the exogenous application of either methyl jasmonate or salicylic acid has no such effect (Moglia et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These are synthesized by the phenylpropanoid pathway (Ververidis et al, 2007) and impart pigmentation to flowers (Tanaka et al, 2008), provide protection against damage by UV radiation (Izaguirre et al, 2007) and insects (Thoison et al, 2004;Diaz Napal et al, 2009), as well as act as signaling molecules (Kobayashi et al, 2004). About 20% of the carbon fixed in photosynthesis is directed into this pathway, which produces the majority of phenolic compounds found in nature.…”
mentioning
confidence: 99%